Pengaruh Fasilitas Parkir Terhadap Perilaku Konsumen Dimoderasi Oleh Brand Image Minimarket di Kota Pekanbaru - Agnes Alvionita; Maha Martabar Mangatas Lumbanraja; Sri Wahyuni Wildah (Forum Kerjasama Pendidikan Tinggi, 2022)
The existence of which there are a number of concerns from minimarket business actors, with the imposition of additional parking fees on consumers will reduce the potential income for the modern minimarket. For this reason, other intervention efforts from business actors are needed to be superior, which in this study is strengthened by the strengthening of the brand image for the minimarket consumers. Thus, the symbol logo and name and appearance will be more easily recognized and trusted by the public. This research is a quantitative study using the SEM-PLS analysis technique on primary data in the form of a questionnaire instrument which was distributed to 97 samples representing the population, namely the people of Pekanbaru City. The findings in this study indicate that the parking facility provided by the manufacturer plays an important role for minimarket consumers in Pekanbaru. And because of that, Minimarket Management and Marketers who are related to the minimarket business, whether located in Pekanbaru or Riau Province, can even represent real conditions in Indonesia, must pay attention to the availability of convenient parking facilities so that they can provide direction for consumers. to be able to choose the products or services available in their business units. In addition, the facts in this study which show that the factor of cheaper parking retribution costs will have a positive impact on consumers, as has been stated in the background of the results of news clippings quoted.